Tropospheric delay effects on relative GPS height determination - Mohd. Zaki, Mohd. Zahlan; Kamarudin, Md. Nor (USM, 2005)
In the global positioning system (GPS) surveying for point positioning, one of the principal limiting error source is incorrect modeling of the delay experienced by GPS signal propagating through the electrically neutral atmosphere, usually referred to as the tropospheric delay. This paper concentrates on showing the result of an experimental work that has been conducted by integrating the Malaysian Active GPS Station (MASS) data and ground meteorological observations to analyze the variation occur to the GPS height determination due to the tropospheric delay. Four individual satellites are selected to assist the analysis due to their availability during the observations period. The result of introducing a Saastamoinen tropospheric model to the data shows a delay variation for up to 20 meter in pseudorange which causes an error up to 5 meter of height component. This paper verify that the integration of ground meteorological observations and GPS lead to a better understanding of the tropospheric delay to the GPS signal and improve the GPS height accuracy.